2021
DOI: 10.3390/life11030182
|View full text |Cite
|
Sign up to set email alerts
|

How Do Inflammatory Mediators, Immune Response and Air Pollution Contribute to COVID-19 Disease Severity? A Lesson to Learn

Abstract: Inflammatory and immune processes are defensive mechanisms that aim to remove harmful agents. As a response to infections, inflammation and immune response contribute to the pathophysiological mechanisms of diseases. Coronavirus disease 2019 (COVID-19), whose underlying mechanisms remain not fully elucidated, has posed new challenges for the knowledge of pathophysiology. Chiefly, the inflammatory process and immune response appear to be unique features of COVID-19 that result in developing a hyper-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 198 publications
(298 reference statements)
1
17
0
Order By: Relevance
“…MDSCs themselves contribute to inflammation and coagulation by producing IL‐1β, TNF‐α, IL‐6 and IL‐8. 39 Takano et al reported that PMN‐MDSCs are positively correlated with IL‐8 levels in patients with COVID‐19 and that IL‐8 plays a role in the recruitment of PMN‐MDSCs to peripheral blood following the onset of severe COVID‐19. 31 Increased IL‐1β, TNF‐α, IL‐6 and IL‐8 levels are associated with increased CRP, D‐dimer and ferritin, causing severe inflammation and coagulation in COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDSCs themselves contribute to inflammation and coagulation by producing IL‐1β, TNF‐α, IL‐6 and IL‐8. 39 Takano et al reported that PMN‐MDSCs are positively correlated with IL‐8 levels in patients with COVID‐19 and that IL‐8 plays a role in the recruitment of PMN‐MDSCs to peripheral blood following the onset of severe COVID‐19. 31 Increased IL‐1β, TNF‐α, IL‐6 and IL‐8 levels are associated with increased CRP, D‐dimer and ferritin, causing severe inflammation and coagulation in COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…In viral infections including SARS‐CoV‐2, TNF‐α causes elevated serum ferritin and LDH levels, as well as thrombocytopenia, lymphopenia and haemolysis. MDSCs themselves contribute to inflammation and coagulation by producing IL‐1β, TNF‐α, IL‐6 and IL‐8 39 . Takano et al reported that PMN‐MDSCs are positively correlated with IL‐8 levels in patients with COVID‐19 and that IL‐8 plays a role in the recruitment of PMN‐MDSCs to peripheral blood following the onset of severe COVID‐19 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to air pollutants is associated with the generation of reactive oxygen species (ROS) and pulmonary inflammation, resulting in adverse health effects such as asthma and decreased lung function [ 45 , 46 ]. Chronic exposure to air pollutants results in degradation of multiple body systems, including the respiratory and immune systems that are largely involved in COVID-19 response [ 47 , 48 ]. This inflammatory response is partially mediated by TLRs, a key portion of the physiological response to SARS-CoV-2 [ 12 ••, 13 ••, 49 ].…”
Section: Epigenetic Perturbations Of Immune Pathways By Environmental...mentioning
confidence: 99%
“…Besides ventilation-perfusion mismatch, intravascular coagulation and alveolar edema, COVID-19 ARDS is a very complex disease, with intrapulmonary shunting, impaired lung diffusion, inflammation, etc. [103][104][105][106][107][108][109]. We cannot expect that early oxygen therapy and pulmonary edema treatments can prevent every COVID-19 patient from the development of ARDS.…”
Section: Clinical Outlookmentioning
confidence: 99%